An Empirical Evaluation of Investment Income under the Equity Method of Accounting. Issue 2 (21st December 2017) - Lai, Cheng; Wu, Jingjing; Mo, Caihua; Zhou, Hua
Abstract: This study investigates the valuation implications of equity method earnings among Chinese listed firms, which are often perceived by the Chinese business press of employing the equity method to avoid reported losses. Our results show that firms with declining core earnings are more likely to have equity method investments than firms with increasing core earnings. Also, firms with lower core earnings report higher equity method earnings. Moreover, equity method earnings do not improve earnings persistence but are found to be relevant. Investors act as if they naively fixate on equity method earnings. A portfolio constructed on the basis of core earnings and equity method earnings generates a hedged return of 8%. Abstract : This study assesses the valuation implications of equity method earnings in China. We find that equity method earnings do not improve overall earnings persistence, yet they are deemed relevant by the stock market. Investors act as if they naively fixate on equity method earnings. Indeed, we show that a portfolio based on equity method earnings and core earnings generates a hedged return of 8%.